Some Topological Properties of Fuzzy Antinormed Linear Spaces - Ljubiša D. R. Kočinac (Journal of Mathematics)
The definition of fuzzy antinorm is modified. Some topological properties of finite dimensional fuzzy antinormed linear space are studied. Fuzzy anticonvergence and statistical fuzzy anticonvergence are defined and their properties are studied. We also discuss some boundedness properties in fuzzy antinormed linear spaces.